Evaluasi Implementasi dan Aktualisasi Usaha Pisang Crispy Berdasarkan Analisis SWOT - Sugama, Meiziri Panji Rapi; Beni, Sabinus; Hapsari, Veneranda Rini; Siokalang, Maria Angela (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study aims to evaluate the implementation and actualization of the business strategy of Crispy Banana using SWOT analysis. The method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. Data analysis is performed qualitatively with the stages of data reduction, data presentation, and conclusion drawing. Research results show that strengths lie in product taste, affordable prices, and attractive packaging. Weaknesses include product durability and flavor variety. Opportunities exist in digital promotion and the interest of student consumers, while threats come from competition and changing market trends. The SWOT matrix is used as a basis for development strategies such as digital marketing expansion, flavor innovation, and efficiency improvement. This implementation is expected to enhance competitiveness and business sustainability